Quantifying the cost of in-kind contributions to a multidonor-funded health research capacity-building programme: the case of the Consortium for Advanced Research Training in Africa. Issue 6 (7th June 2020) - Fonn, Sharon; Hu, Jia; Igumbor, Jude Ofuzinim; Gatoto, Duncan; Muula, Adamson; Ezeh, Alex
Abstract : Introduction: There are significant investments in health research capacity development in the 'global-south'. The monetary value of contributions from institutions running these programmes is not known. Methods: Using the Consortium for Advanced Research Training in Africa (CARTA) as a case study we estimate in-kind contributions made by consortium members. We measured unpaid hours of labour contributed by consortium members and converted this to full-time equivalents. We assigned a monetary value to the time contributed by staff based on salaries by seniority and region. We estimated the monetary value of the contribution made by the African institutions that hosted CARTA events by comparing the difference in cost between university-hosted events with those held in commercial venues. We calculated the foregone overhead costs associated with hosting the CARTA secretariat. We excluded many costs where data were difficult to verify. Results: Annually, CARTA member institutions committed a minimum of 4.3 full-time staff equivalents that are not funded by the grants. CARTA's annual in-kind contribution represents at least 20% of total annual donor expenditure. African institutions accounted for 82.9% of the in-kind labour contribution and 91.6% of total in-kind contribution. Conclusion: The consortium's institutions and academic and non-academic staff make significant contributions to ensure the effective implementation of donor-funded programmes. This is not unique to CARTA. These contributions are usually not counted, often not recognised at institutional level nor remunerated through grants. Knowing these costs would allow for sustainability appraisals and cost-benefit assessments. This paper offers a method of how to measure these contributions and begins a discussion around this.